Asymptomatic hyponatremia precipitated by COVID-19 pneumonia. Issue 6 (2nd November 2021) - Chittal, Abhinandan R.; Rao, Shiavax J.; Lakra, Pallavi; Zulty, Mary E.
ABSTRACT: COVID-19, also known as SARS-CoV-2, which originated in China in late 2019, has spread rapidly resulting in a global pandemic. COVID-19 has been linked to many different clinical manifestations, including hyponatremia. The cause of hyponatremia in acute COVID-19 infection is speculated to be multifactorial, including syndrome of inappropriate antidiuretic hormone secretion (SIADH), thought to be a result of inflammatory cytokines (Interleukin-6) and/or related to the gastrointestinal symptoms of this infection. SIADH in the setting of COVID-19 pneumonia is an established complication of this disease. This is the case of an 81-year-old woman with a history of hypertension, on thiazide diuretic, initially presented after a fall in the setting of COVID-19 pneumonia. She was treated with remdesivir and dexamethasone and then discharged to a rehab facility with normal labwork, including a sodium of 137 mmol/L. Two weeks later, routine labwork identified hyponatremia of 111 mmol/L. Her vital signs were normal, she was euvolemic on exam and alert/oriented with no complaints. Investigations into the etiology of her hyponatremia included a urine sodium of 72 mmol/L, serum osmolality of 231 mOsm/kg, urine osmolality of 454 mOsm/kg. We diagnosed hypo-osmolar hyponatremia due to SIADH. Management included fluid restriction and then tolvaptan, which ultimately corrected the serum sodium to 134 mmol/L. As COVID-19 is a new infection, little is known regarding its impact on electrolyte imbalances. Our patient recovered from pneumonia, then later developed severe hyponatremia possibly secondary to the lasting effects of inflammation in her lungs.